Insomnia and excessive daytime sleepiness in medical students: consequences of the use of technologies? - da Silva Cardoso, Gabriela Miloch [UNESP]; da Silva, Mariana Pires Ferreira Novaes [UNESP]; de Castro Corrêa, Camila; Weber, Silke Anna Theresa [UNESP] (Thieme, 2022)
Objective: To analyze the relation among insomnia, excessive daytime sleepiness and the excessive use of technologies in medical students. Methods: The study was approved by the Local Ethics Committee of the institution. Students from the 1st and 2nd year of medical graduation students participated. Three questionnaires were used: Sleep Time-Related Information and Communication Technology, Insomnia Severity Index and the Epworth Sleepiness Scale. The data were described and compared by gender and year of graduation by the Students T Test, and correlated to the use of technology, insomnia and excessive daytime sleepiness by Pearsons Correlation (adopted the significance level of p <0.05). Results: 106 students (41 male) participated, expressing perception of insomnia in 76.4%, 34% with excessive daytime sleepiness, and 38.3% had a high use of technology related to sleep. There was a correlation between the use of technologies both with insomnia (r = 0.393; p = < 0.001), as well as with excessive daytime sleepiness (r = 0.228; p = 0.019). Conclusion: An important frequency of insomnia was found associated with the excessive use of technologies at the bed, with repercussions of daytime sleepiness. This demonstrates the importance of actions to raise awareness and education about correct sleep hygiene in medical students.
Keywords: Medical; Sleep; Students; Technology